(untitled) (International Journal of Ayurveda and Pharma Research, 2022)
Menstruation is a normal body function initiated in response to ovarian hormones which inturn is controlled by the hypothalamo-pituitary axis. Menstrual patterns can also be an indicator of health status of the reproductive tract and self-awareness of the reproductive well-being. The causes may be varying right from disturbances in hypothalamus, pituitary, ovary and uterus influencing general health. Hence women who do not get their menstruation on the expected date will try to consume food/medicines whichever they think will induce menstruation at the earliest. The choice of medication to do so is very limited and there are no certain medicines which a gynecologist can prescribe to her patient’s in order to bring the menstruation at the earliest which is not expected at the date. So it will be a great boon to the woman if it can be replaced by natural remedies with no side effects. Present study has been undertaken to evaluate the combined effect of Jeeraka and Krishna jeeraka choorna in the induction of menstruation. 20 patients complaining of Anartava (amenorrhea) of more than 40 days, attending the OPD & IPD of Prasuti Tantra & Stree Roga Department, Sri Dharmasthala Manjunatheswara Ayurveda Hospital, Kuthpady, Udupi, were selected for the study. Based on the assessment criteria, the data was graded and statistically analysed using wilcoxon’s signed rank test and paired T test. After the intervention it was observed that the medicine is having good action in induction of menstruation (85%).